Individual and regional association between socioeconomic status and uncertainty stress, and life stress: a representative nationwide study of China - Tingzhong Yang; Xiaozhao Y Yang; Lingwei Yu; Randall R. Cottrell; Shuhan Jiang (BMC, 2017)
Abstract Background Many studies have examined the association between socioeconomic status (SES) and mental stress. Uncertainty stress is a prominent aspect of mental stress. Yet no research has ever empirically analyzed the impact of SES on uncertainty stress. Methods Students were identified through a multistage survey sampling process including 50 universities. Each student participant completed the Global Health Professions Student Survey (GHPSS) on Tobacco Control in China. Regional variables were retrieved from the National Bureau of Statistics database. Both unadjusted and adjusted methods were considered in the analyses. Results Among the 11,942 participants, severe uncertainty stress prevalence was 19.6%, while severe life stress prevalence was 8.6%. Multilevel logistic regression showed that most SES variables were associated with uncertainty stress. Students with "operation and commercial work" as mother's occupation and "rural or township" as family location exhibited a higher prevalence of severe uncertainty stress. Lower family income and original region gross domestic products (GDP) were also associated with higher severe uncertainty stress prevalence. However, only father's occupation was correlated with life stress. Conclusions Based on the literature review, this is the first empirical study examining the impact of SES on uncertainty stress in China and elsewhere in the world. Our research underscores the importance of decreasing socioeconomic inequalities in controlling excessive uncertainty stress.